2016
DOI: 10.5543/tkda.2015.93237
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness parameters associated with vitamin D deficiency and supplementation in patients with normal cardiac functions

Abstract: Vitamin D supplementation has beneficial effects on arterial stiffness. Arterial stiffness parameters may aid in the assessment of cardiovascular risk in patients with vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The findings of the present study were similar to a previous study that demonstrated significant decrease in pulse wave velocity from baseline (6.8 [1.55] m/s vs. 6.4 [1.3] m/s) following oral administration of 50,000 IU of Vitamin D 3 /week for 8 weeks followed by 2000 IU/day for 4 weeks in patients with Vitamin D deficiency. [17]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the present study were similar to a previous study that demonstrated significant decrease in pulse wave velocity from baseline (6.8 [1.55] m/s vs. 6.4 [1.3] m/s) following oral administration of 50,000 IU of Vitamin D 3 /week for 8 weeks followed by 2000 IU/day for 4 weeks in patients with Vitamin D deficiency. [17]…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated significant reduction in augmentation index from baseline (31 [14.5]% vs. 23 22%) with oral Vitamin D 3 supplementation (50,000 IU/week for 8 weeks and maintenance dose of 2000 IU/day for 4 weeks) in patients with Vitamin D deficiency. [17] However, a randomized controlled study showed no change in augmentation index with Vitamin D supplementation (2500 IU/day for 4 months) in postmenopausal women with serum Vitamin D levels ranging between 10 and 60 ng/ml. [14] Similarly, another randomized controlled trial evaluating the effect of Vitamin D supplementation (400 IU or 2500 IU/day for 6 months) showed no difference in aortic systolic blood pressure, aortic pulse pressure, and augmentation index between high dose and low dose Vitamin D group in healthy postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that vitamin D supplementation improves vascular functions and reduces oxidative stress in vitamin D deficient patients. [62][63][64] A randomized controlled trial has demonstrated the beneficial effects of calcium and vitamin D supplementation in reducing cancer risk in postmenopausal women. 65 There are also conflicting results with the use of vitamin D supplementation in prevention of cardiovascular diseases or cancer.…”
Section: Vitamin D Deficiencymentioning
confidence: 99%